An approach towards the construction of the tetracyclic skeleton of palhinine alkaloids. Issue 16 (17th July 2020) - Han, Congcong; Chen, Yang; Ching, Yin-Cheung; Lee, Chi-Sing; He, Shuzhong
Abstract : A bifunctional Lewis acid catalyzed Diels–Alder/carbocyclization cascade process was developed for the rapid construction of the tetracyclic core of palhinine alkaloids. Abstract : A concise synthesis of the tetracyclic skeleton of palhinine alkaloids is described. The approach features a bifunctional Lewis acid promoted Diels–Alder/carbocyclization cascade for the rapid construction of the isotwistane (tricyclo[4.3.1.0 3, 7 ]decane) core. This key reaction is highly diastereoselective and could be carried out on gram scale. The cyclization product already possesses the completed ring system of palhinine alkaloids and could potentially be further functionalized to palhinine A.